The Human MTCH2 Protein Has a Negative Effect On the Influenza a Virus Replication - TURAN, KADİR (My University, 2021)
Influenza A viruses have a segmented genome consists of eight single-stranded RNA molecules. Viral replication and transcription are carried out by viral RNA polymerase (RdRP), which consists of PB2, PB2 and PA subunits. During viral infection, RdRP and other viral proteins interact with several host proteins to perform their functions. In this work, mitochondrial carrier homolog 2 (MTCH2) protein, which was found to be associated with viral PA protein by yeast two-hybrid assay, was investigated its importance in terms of viral replication. In order to detect the effects of MTCH2 on virus replication in HeLa and HEK293 cells, the protein level was artificially changed. RNA interference and CRISPR/Cas9 techniques were used for down-regulation of the MTCH2. To increase the MTCH2, the HEK293 cells were transfected with pCHA-MTCH2 plasmid. The cells with altered MTCH2 transcript/protein level were infected with influenza A/WSN and A/DkPen viruses, and the viral replication was evaluated by detection of viral RNA/proteins with qPCR/Western blot techniques and plaque assays. In addition, the RdRP activities in these cells were determined by mini-replicon tests. A significant increase of viral mRNA/protein was observed in knockdown HeLa. It was shown that avian influenza A/DkPen replication was affected more. The over-expression of MTCH2 in HEK293 cells had a negative effect on the viral RdRP. These results showed that the MTCH2 is a negative cellular factor for influenza A virus. Although deletion of MTCH2 genes was detected in HEK293 cells knocked out by CRISPR/Cas9 technique, no negative effect on viral replication was observed. This situation is thought to be caused by heterozygosity or some other factors. From these results, it was concluded that the MTCH2 protein functions as a negative regulation factor for influenza A viruses. This work was supported by a grant of the Scientific and Technological Research Council of Turkey (SBAG-112S518).Keywords: Influenza a Viruses, MTCH2 Protein, Viral Rna Polymerase, PA Protein
Keywords: Yaşam Bilimleri; Sağlık Bilimleri; Life Sciences; Health Sciences; Klinik Tıp (MED); Yaşam Bilimleri (LIFE); Clinical Medicine (MED); Life Sciences (LIFE)